ANALYSIS OF THE AUDITOR'S DURATION OF RELATIONSHIP WITH THE AUDITEE ON AUDITOR'S INDEPENDENCE - Atika Kiki Maharani; Ghina Fitri Ariesta (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
This study seeks to find out whether the length of the auditor's relationship with the auditee affects auditor independence and to find out what factors affect auditor independence. The method used in this study is qualitative with secondary data sources derived from previous research journals, books containing research topics, theses, and other sources related to research. The results of this study indicate that the length of the auditor's relationship with the auditee has a negative effect on auditor independence and the factors that affect auditor independence are the size of the Public Accounting Firm (KAP), the length of the auditor's relationship with the client, giving hope other than auditing, competition between KAPs.